Comparing Efficiency Between Cooperative and Non-cooperative Farms: A Case of Sugar Beet Farmers of West Azerbaijan, Iran. (April 2019) - Zamani, Omid; Mojaverian, Mojtaba; Nader, Hemen
Achieving a higher level of efficiency is one of the main goals of agricultural cooperatives. However, it is not clear whether the cooperative farms are more efficient than non-cooperative farms. In this line, the present study aims to compare the performance of the cooperative and non-cooperative farms by employing the super-efficiency data envelopment analysis (DEA). To this end, a survey was designed to collect data from the sugar beet farmers of West Azerbaijan province in Iran. Overall, 30 samples from cooperative farms and 29 samples from non-cooperative farms were interviewed randomly. Then, the efficiency scores for both sample groups were calculated separately. Finally, the average of efficiency scores was compared by using the non-parametric approach (Mann–Whitney test). The study findings revealed that the average efficiency scores of cooperative farms are significantly higher than non-cooperatives farms. Additionally, the results emphasized the economy of scale among the cooperative farms. Overall, we found that performance of sugar beet cooperatives is substantially better than the non-cooperatives; thus, supporting the cooperatives is recommended in the study area in order to improve the efficiency.